The Tuition Battle at Mexico’s National University - Levy, Daniel; Arenas, Jorge (International Higher Education, 1999)
The battle now raging over tuition at Mexico’s National University (Universidad Nacional Autónoma de México—UNAM) echoes battles of yesteryear while also reflecting new realities of Mexico in both higher education and politics. On March 15th of this year, the University’s council passed the General Bylaw on Payments, breaking a tradition of virtually no tuition for the institution’s student body of roughly 300,000 (which includes those at the “preparatory” preuniversity level). By April, UNAM found itself paralyzed by a student strike, and some “solidarity” strikes had spread to other institutions. For weeks, the strike and related issues have been front-page news in Mexico.